Knowledge and Awareness of the orthodontic triage and its uses among dental healthcare professionals - a cross-sectional study - Fizzah Ikram; Rashna Hoshang Sukhia; Mubassar Fida (BMC, 2024)
Abstract Introduction In orthodontics, the triage system is used to assess the preadolescents to rule out interventions needed earlier and to assess the nature of orthodontic problems as complex or moderate. The objective of this study was to determine the knowledge and awareness of orthodontic triage and its uses among dental healthcare professionals (DHCP). Materials and methods A triage awareness questionnaire (TAQ) was formulated and validated as reliable by a panel of five orthodontic specialists which was then circulated online among 400 DHCP. The questionnaire consisted of nine sections that assessed the current knowledge and usage of orthodontic triage among the dental community. Frequencies and percentages were reported for all categorical variables. Chi-square was used to assess the association among the variables. Results The response rate was 28.2% with the majority of participants being general dentists. Regarding the knowledge and use of triage, 40% of DHCP were only familiar with the word "orthodontic triage" while being unaware of how it works and 79% denied using orthodontic triage. Regarding the management of anomalies, 42% of DHCP preferred extraction as the management of supernumerary teeth (p = 0.013). Practitioners belonging to private setups performed visual inspection in growing patients for assessment of their facial features (p = 0.012). Clinicians with more than one year of experience referred young patients to orthodontic specialists for the management of crossbite (p = 0.024). Younger clinicians (25-35 years) with more than one year of experience referred adult patients to orthodontists for correction of their unesthetic smile (p = 0.013). Conclusions This paper provides foundational data for the development of future policies and protocols supporting structured, evidence-based approaches to patient management via use of orthodontic triage. This study underscores the importance of targeted educational interventions to enhance understanding and implementation of orthodontic triage principles in clinical practice. Further probing is necessary to discern the disparity between understanding the orthodontic triage and effective employment of its components among practicing dental healthcare professionals.